Composite modified δ-MnO2 cathode material, three-dimensional thick-coated electrode, its preparation method and application

CN123018177APending Publication Date: 2026-10-30XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285363.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30
Patent Text Reader

Abstract

This invention discloses a composite modified δ-MnO2 cathode material and a three-dimensional thick-coated electrode. It also discloses the preparation method and application of the composite modified δ-MnO2 cathode material and the three-dimensional thick-coated electrode. The composite modified δ-MnO2 cathode material has metal ions pre-embedded in the δ-MnO2 layers and is coated with an amorphous metal oxide layer. The metal ions are K+. + Cu 2+ Na + Any one of the following, wherein the thickness of the metal oxide coating layer is 2nm~10nm. The cathode material of the present invention significantly improves reaction kinetics and rate performance, and enhances cycle stability; the prepared electrode, by constructing a three-dimensional conductive network, greatly reduces ion diffusion tortuosity, thereby increasing the active material loading and battery energy density while ensuring excellent rate performance and high-current cycle stability, enabling the cathode material to simultaneously possess long cycle life, high rate performance, and high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of zinc-ion battery technology, and relates to composite modified δ-MnO2 cathode material and three-dimensional thick-coated electrode. This invention also relates to the preparation method and application of the above-mentioned composite modified δ-MnO2 cathode material and three-dimensional thick-coated electrode. Background Technology

[0002] Aqueous zinc-ion batteries have become a research hotspot in the field of large-scale energy storage due to their advantages of high safety, low cost, and environmental friendliness. Layered δ-MnO2, as a typical cathode material, has a high theoretical capacity, but faces three major bottlenecks in practical applications: First, poor bulk structure stability: the layered structure is prone to collapse during cycling, Mn dissolves, and Zn... 2+ High diffusion resistance and slow reaction kinetics lead to short cycle life and poor rate performance; secondly, severe interfacial side reactions: irreversible basic zinc sulfate and other byproducts are easily generated at the electrode-electrolyte interface, which exacerbates capacity decay; thirdly, the electrode energy density is limited: conventional thin electrodes have low active material loading, resulting in insufficient overall battery energy density; traditional thick electrodes have tortuous ion diffusion paths and poor transport kinetics, making it impossible to achieve both high loading and high rate performance.

[0003] Existing technologies have proposed some improvement solutions to the above problems, but all of them have the limitation of single-dimensional optimization: 1. Metal ion pre-intercalation strategies can expand interlayer spacing and stabilize the structure to some extent, but most schemes only focus on lattice manipulation, neglecting electronic structure optimization, and cannot improve interfacial side reactions. The paper "A Superior δ-MnO2 Cathode and a Self-Healing Zn-δ-MnO2 Battery" (ACS Nano, 2019, Vol. 13, No. 9) discloses Na... + The preparation method of pre-intercalating δ-MnO2 with water molecules can improve the cycling stability of the material to some extent by expanding the interlayer spacing and stabilizing the layered framework through pre-intercalation. However, this method only focuses on the control of lattice spacing and does not synergistically optimize the electronic structure of the material. Furthermore, it does not improve the manganese dissolution and side reaction problems at the electrode-electrolyte interface, resulting in a significant bottleneck in performance improvement.

[0004] 2. Coating modification can alleviate interfacial side reactions, but conventional coating methods are difficult to achieve atomically uniform coverage, which can hinder ion transport. The paper "Enhanced Kinetics and Stability of Zn-MnO2 Batteries with a Multifunctional TiO2 Coating" (Advanced Materials, 2025, Vol. 37, No. 2505082) discloses a modification scheme for coating MnO2 cathodes with TiO2 nanolayers. This coating can act as a physical barrier to alleviate interfacial side reactions and inhibit manganese dissolution. However, conventional wet coating combined with annealing processes are difficult to achieve precise control of atomic-level thickness and conformal coverage. Excessive coating thickness can hinder the cross-interface transport of zinc ions, thus degrading the rate performance of the material.

[0005] 3. Thick electrode design can improve energy density, but thick electrodes prepared by traditional coating processes have high tortuosity and severe performance degradation under high current. The review article "Recent Developments of Preintercalated Cathodes for Rechargeable Aqueous Zn-Ion Batteries" (Energy Technology, Vol. 8, No. 12, 2020) systematically summarizes the research progress of existing preintercalation modification technologies. It points out that most current mainstream preintercalation strategies only focus on interlayer spacing expansion or conductivity improvement, lacking synergistic design of interlayer spacing control and electronic structure optimization, resulting in the inability to simultaneously improve the ion diffusion and electron transport dynamics of the material. Furthermore, considering the current research status of coating modification and thick electrode design, various modification routes generally suffer from the limitation of single-dimensional optimization. Coating modification is difficult to balance interface stability and ion transport dynamics. Thick electrodes prepared by traditional coating processes have high tortuosity and severe performance degradation under high current. The lack of multi-dimensional integrated design of bulk structure control, interface stabilization, and electrode structure optimization makes it impossible to simultaneously solve the triple problems of short cycle life, poor rate performance, and low energy density of δ-MnO2 cathodes, thus restricting the practical application of aqueous zinc-ion batteries.

[0006] Therefore, there is an urgent need for an integrated modification scheme that can simultaneously achieve structural stability, interface optimization, and improved thick electrode dynamics, while addressing the triple challenges of cycle life, rate performance, and energy density of the δ-MnO2 cathode. Summary of the Invention

[0007] The first objective of this invention is to provide a composite modified δ-MnO2 cathode material that solves the problems of unstable MnO2 cathode structure, short cycle life, and severe interfacial side reactions in the prior art.

[0008] The second objective of this invention is to provide a method for preparing the above-mentioned composite modified δ-MnO2 cathode material.

[0009] A third objective of this invention is to provide a three-dimensional thick-coated positive electrode.

[0010] The fourth objective of this invention is to provide a method for preparing the above-mentioned three-dimensional thick-coated positive electrode.

[0011] The fifth objective of this invention is to provide an aqueous zinc-ion battery.

[0012] The first technical solution adopted in this invention is a method for preparing composite modified δ-MnO2 cathode material, which is specifically implemented according to the following steps: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Step 3: Perform the hydrothermal reaction; Step 4: Obtain the precipitate by centrifugation and washing; Step 5: Vacuum dry the precipitate to obtain δ-MnO2 powder pre-embedded with metal ions; Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material.

[0013] The first technical solution of this invention is also characterized by: In step 1, the molar ratio of manganese source to pre-intercalated metal salt is 1:(0.05~0.15); the principle for selecting manganese source is that it can synthesize δ-MnO2 by hydrothermal method, and the pre-intercalated ion of pre-intercalated metal salt is any one of potassium ion, copper ion, and sodium ion.

[0014] Step 2 is as follows: Add the manganese source and the pre-intercalated metal salt to deionized water and stir. Stir at a stirring speed of 300 rpm to 500 rpm for 20 min to 40 min until the manganese source and the pre-intercalated metal salt are completely dissolved to obtain a uniform and transparent mixed solution. The volume ratio of the manganese source to the deionized water is 1 mmol: (7 to 9) mL. Step 3 is as follows: Seal the mixed solution of manganese source and pre-intercalated metal salt in a hydrothermal reactor, then place the reactor in a forced-air drying oven and keep it at 160℃~200℃ for 10h~14h. After the reaction is completed, turn off the oven and let it cool naturally to room temperature, then take out the reaction product. Step 4 is as follows: Transfer the mixture obtained after the hydrothermal reaction to a centrifuge tube, put it into a high-speed centrifuge, and centrifuge at 8000rpm~12000rpm for 5min~10min to separate the precipitate and the supernatant. Take the precipitate and wash it alternately with deionized water and anhydrous ethanol 2~4 times to remove residual unreacted impurity ions. Step 5 specifically involves transferring the washed precipitate to a vacuum drying oven and drying it under vacuum at a temperature of 50℃~70℃ for 10h~14h to remove residual solvent and obtain metal ion pre-intercalated δ-MnO2 powder. Step 6 specifically involves: spreading the metal ion pre-embedded δ-MnO2 powder obtained in step 5 in the closed vacuum process chamber of the atomic layer deposition equipment, and alternating metal source pulse and oxygen source pulse reactions at a deposition temperature of 80℃~150℃. By controlling the number of deposition cycles, the coating layer thickness is adjusted to 2nm~10nm to obtain an amorphous metal oxide layer coated metal ion pre-embedded δ-MnO2 cathode material, i.e., a composite modified δ-MnO2 cathode material.

[0015] In step 6, the coating thickness is 2nm~10nm.

[0016] The second technical solution adopted in this invention is a composite modified δ-MnO2 cathode material, prepared according to the above-described preparation method for composite modified δ-MnO2 cathode material. Metal ions are pre-embedded in the δ-MnO2 layers, and the surface is coated with an amorphous metal oxide layer. The metal ions are K+. + Cu 2+ Na + Any one of them, the thickness of the metal oxide coating layer is 2nm~10nm.

[0017] The third technical solution adopted in this invention is a three-dimensional thick-coated positive electrode, comprising the above-mentioned composite modified δ-MnO2 positive electrode material.

[0018] The fourth technical solution adopted in this invention is a method for preparing a three-dimensional thick-coated positive electrode, which is implemented according to the following steps: S1. Weigh out the composite modified δ-MnO2 cathode material, composite conductive agent and binder according to the proportion; S2. The composite modified δ-MnO2 cathode material, composite conductive agent and binder are added to the dispersion solvent and mixed. The mixture is stirred until it is uniform to obtain the electrode slurry. S3. Under the assistance of a magnetic field, the electrode paste is coated onto a conductive current collector that is resistant to electrolyte corrosion and then dried to obtain an electrode sheet. S4. Press and cut the electrode sheet to obtain a three-dimensional thick-coated positive electrode.

[0019] The fourth technical solution adopted in this invention is further characterized by: The mass ratio of the composite modified δ-MnO2 cathode material to the composite conductive agent is 19:1 to 99:1, and the binder accounts for 8% to 12% of the total mass of the composite modified δ-MnO2 cathode material and the composite conductive agent. The composite conductive agent is composed of sheet-like magnetic conductive material and particulate conductive carbon, with the sheet-like magnetic conductive material accounting for 40% to 70% of the total mass of the composite conductive agent, and the remainder being particulate conductive carbon.

[0020] S3 specifically involves uniformly coating the electrode slurry onto a conductive current collector resistant to electrolyte corrosion. During the coating process, an external magnetic field perpendicular to the plane of the current collector is applied below it, with a magnetic field strength of 0.5T~2T. This induces the sheet-like magnetic conductive material in the slurry to align perpendicularly to the magnetic field direction, constructing a three-dimensional conductive network and ion transport channels perpendicular to the current collector. Finally, the coating is vacuum dried in a vacuum drying oven at a temperature of 80℃~120℃ for 12h~24h to completely remove the dispersing solvent. The coating thickness is 100μm~200μm.

[0021] The fifth technical solution adopted in this invention is an aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is a three-dimensional thick-coated positive electrode, the negative electrode is a zinc sheet, the separator is glass fiber, and the electrolyte is a mixed aqueous solution of zinc salt and manganese salt.

[0022] The beneficial effects of this invention are: 1. Synergistic Regulation of Lattice and Electronic Structure: A one-step hydrothermal method incorporates composite modification into the interlayer of δ-MnO2, acting as an "ion pillar" to widen the interlayer spacing, inhibit structural collapse and Mn dissolution, and reduce Zn content. 2+ Diffusion resistance; on the other hand, by adjusting the covalent degree of the Metal-O bond, optimizing the p-band center of the O atom, and balancing the H... + Adsorption and desorption capacity, improving H + Intercalation capacity contribution significantly improves reaction kinetics and rate performance; 2. Atomic-level interface stability optimization: The amorphous metal oxide layer prepared by atomic layer deposition technology can achieve atomic-level uniform coating, which can not only isolate the active material from direct contact with the electrolyte and suppress interfacial side reactions, but also promote zinc ion diffusion through the disordered channels and defects of the amorphous layer, while buffering the charge and discharge volume stress, further improving cycle stability. 3. Breakthrough in high-load thick electrode dynamics: Magnetic field induces vertical orientation of sheet-like conductive agent to construct a three-dimensional conductive network, optimizing the tortuous diffusion path of traditional thick electrodes into a vertically direct channel, significantly reducing the tortuosity of ion diffusion, and ensuring excellent rate performance and high-current cycling stability while increasing the loading of active material and improving battery energy density. 4. Multi-dimensional synergistic adaptation to various scenarios: The three technologies synergistically modify the cathode material from three dimensions: bulk phase, surface interface, and electrode structure, enabling the cathode material to simultaneously possess long cycle life, high rate performance, and high energy density. The preparation process is controllable and can be scaled up, making it suitable for large-scale energy storage and photovoltaic-storage integrated application scenarios. Detailed Implementation

[0023] The present invention will now be described in detail with reference to specific embodiments.

[0024] The preparation method of the composite modified δ-MnO2 cathode material of the present invention is carried out according to the following steps: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; The molar ratio of manganese source to pre-intercalated metal salt is 1:(0.05~0.15), ensuring that the amount of pre-intercalated ions can achieve the effect of lattice and electronic structure regulation without excessively damaging the layer structure.

[0025] The principle for selecting manganese sources is that they can synthesize δ-MnO2 via hydrothermal methods. Any one or more of permanganate, manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate, mixed in any proportion, will not affect the performance of the final material as long as they can synthesize layered δ-MnO2 via hydrothermal methods.

[0026] The pre-intercalated metal salt can be any one of potassium ions, copper ions, or sodium ions. Anions do not affect the pre-intercalation effect or the performance of the final material. The pre-intercalated metal salt can be any one of sulfates, chlorides, nitrates, or acetates. The pre-intercalated metal salt can be any one of K2SO4, CuSO4, or Na2SO4.

[0027] Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Specifically, the manganese source and the pre-intercalated metal salt are added separately to deionized water and stirred at a speed of 300 rpm to 500 rpm for 20 min to 40 min until the manganese source and the pre-intercalated metal salt are completely dissolved, resulting in a uniform and transparent mixed solution. The ratio of manganese source to deionized water volume is 1 mmol: (7~9) mL.

[0028] Step 3: Perform the hydrothermal reaction; Specifically, the manganese source and the pre-intercalated metal salt solution are sealed in a hydrothermal reactor, and then the reactor is placed in a forced-air drying oven. The reaction is carried out at a temperature of 160℃~200℃ for 10h~14h. After the reaction is completed, the oven is closed and the product is naturally cooled to room temperature. The hydrothermal reactor is a conventional piece of equipment in this field, with a stainless steel outer shell and a polytetrafluoroethylene lining.

[0029] Step 4: Obtain the precipitate by centrifugation and washing; Specifically, the mixture obtained after the hydrothermal reaction is transferred to a centrifuge tube, placed in a high-speed centrifuge, and centrifuged at 8000 rpm to 12000 rpm for 5 to 10 minutes to separate the precipitate and supernatant. The precipitate is then washed 2 to 4 times alternately with deionized water and anhydrous ethanol to remove any remaining unreacted impurity ions.

[0030] Step 5: Vacuum dry the precipitate to obtain metal ion pre-intercalated δ-MnO2 powder; The specific process is as follows: the washed precipitate is transferred to a vacuum drying oven and vacuum dried at a temperature of 50℃~70℃ for 10h~14h to remove the residual solvent and obtain metal ion pre-intercalated δ-MnO2 powder material.

[0031] Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material; The coating thickness is 2nm~10nm; Specifically, the metal ion pre-embedded δ-MnO2 powder obtained in step 5 is spread evenly in the closed vacuum process chamber of the atomic layer deposition equipment. At a deposition temperature of 80℃~150℃, metal source pulse and oxygen source pulse reactions are alternately performed. The coating layer thickness is adjusted to 2nm~10nm by controlling the number of deposition cycles, and the metal ion pre-embedded δ-MnO2 cathode material with amorphous metal oxide layer is obtained, namely the composite modified δ-MnO2 cathode material.

[0032] The amorphous metal oxide layer is amorphous TiO2; the titanium source is titanium tetrachloride TiCl4, the oxygen source is deionized water, and the carrier gas and purge gas are high-purity argon; each deposition cycle consists of titanium source pulse, argon purge, oxygen source pulse, and argon purge in sequence.

[0033] Besides titanium oxide, the coating layer of atomic layer deposition can be replaced with other stable metal oxides, as long as it can achieve interface stability and does not hinder ion transport, all of which can achieve similar technical effects.

[0034] Atomic layer deposition (ALD) coating technology can form an atomically uniform amorphous metal oxide layer on the material surface through successive pulse reactions. This layer serves as both an interface barrier and an ion transport function, while also buffering charge and discharge volume stress. Furthermore, it allows for precise control of the coating layer thickness, achieving conformal and uniform coverage and avoiding the defects of uneven thickness and easy agglomeration in traditional wet coating methods.

[0035] This invention employs a one-step hydrothermal method to simultaneously introduce pre-intercalated metal ions into the interlayer of δ-MnO2, achieving pre-regulation of the crystal lattice and electronic structure. The principle is as follows: Composite modified δ-MnO2 cathode material, as the core active material of cathode, undertakes the main capacity contribution. After modification, it has dual regulation and interface stabilization effects. The dual regulation includes lattice regulation and electronic structure regulation. Lattice regulation manifests in the pre-intercalated ions expanding the interlayer spacing of δ-MnO2, reducing the diffusion resistance of zinc ions, and acting as "pillars" to stabilize the layered structure, suppressing structural collapse and manganese dissolution during charging and discharging. Electronic structure regulation manifests in the pre-intercalated ions adjusting the covalence of the metal-oxygen bond, optimizing the p-band center of the oxygen atom, balancing the adsorption and desorption capabilities of hydrogen ions, enhancing the hydrogen ion intercalation capacity, and improving the overall reaction kinetics. The interface stability is manifested in the fact that the amorphous metal oxide coating layer on the surface isolates the active material from direct contact with the electrolyte, inhibits irreversible side reactions at the interface, alleviates manganese dissolution, and buffers the charge and discharge volume stress, further improving cycle stability.

[0036] The advantages of this method are: it completes synthesis and modification in one step, requires no complicated post-processing, has a simple process, low cost, is suitable for large-scale production, and avoids impurities introduced during post-processing, thus ensuring the purity of the material.

[0037] The composite modified δ-MnO2 cathode material of this invention is prepared according to the above steps. Metal ions are pre-embedded in the δ-MnO2 layers, and the surface is coated with an amorphous metal oxide layer. The metal ions are K+. + Cu 2+ Na + Any one of them, the thickness of the metal oxide coating layer is 2nm~10nm.

[0038] The present invention also provides a three-dimensional thick-coated positive electrode, comprising the above-mentioned composite modified δ-MnO2 positive electrode material.

[0039] This invention provides a method for preparing the above-mentioned three-dimensional thick-coated positive electrode, using the above-mentioned composite modified δ-MnO2 positive electrode material as the active material, specifically implemented according to the following steps: S1. Weigh out the active material, conductive agent and adhesive according to the proportions; The mass ratio of the composite modified δ-MnO2 cathode material to the composite conductive agent is 19:1 to 99:1, and the binder accounts for 8% to 12% of the total mass of the composite modified δ-MnO2 cathode material and the composite conductive agent. The composite conductive agent is composed of sheet-like magnetic conductive material and granular conductive carbon, wherein the sheet-like magnetic conductive material accounts for 40% to 70% of the total mass of the composite conductive agent, and the remainder is granular conductive carbon.

[0040] The sheet-like magnetic conductive material can be any one of magnetic graphene or magnetic expanded graphite; the particulate conductive carbon can be replaced by any one or more of conductive carbon black, superconducting carbon, acetylene black, graphene, carbon nanotubes, and Ketjen black in any proportion, as long as it can improve the electrode conductivity and be oriented under a magnetic field.

[0041] Active materials contribute to the battery's capacity, while conductive agents provide the pathway for electron transport. This ratio ensures a sufficient proportion of active materials while constructing a continuous conductive network, balancing energy density and conductivity. It avoids reducing the electrode's energy density by excessive conductive agents crowding out the active materials, and also prevents hindered electron transport by insufficient conductive agents, effectively improving the electrode's rate performance.

[0042] The composite modified δ-MnO2 component provides the core active material for capacity. If the content is too low, the proportion of active material in the electrode will be too low, which will significantly reduce the overall energy density of the electrode and fail to meet the requirements of energy storage devices. If the content is too high, the proportion of conductive agent will be insufficient, and a continuous conductive network cannot be built, which will lead to obstructed electron transport, increased electrode internal resistance, and severe performance degradation under high current.

[0043] Composite conductive agents are used to construct a continuous conductive network inside the electrode, which can compensate for the low electronic conductivity defect caused by the semiconductor properties of δ-MnO2 itself. By constructing a vertically oriented continuous conductive network, the internal resistance of the electrode is reduced, the electron transport efficiency is improved, and thus the rate performance and cycling stability of the electrode under high current are improved.

[0044] The binder is used to bond the active material and the conductive agent, ensuring the mechanical stability of the electrode structure and allowing the active material to adhere tightly to the surface of the current collector. In addition to polyvinylidene fluoride, it can be replaced by any of carboxymethyl cellulose, styrene-butadiene rubber, or polytetrafluoroethylene, as long as it can achieve the function of bonding the active material.

[0045] S2. The composite modified δ-MnO2 cathode material, composite conductive agent and binder are added to the solvent and mixed. The mixture is stirred until it is homogeneous to obtain the electrode slurry. Specifically, the weighed active material, conductive agent and binder are mixed evenly, then added to the dispersion solvent, and stirred at a stirring speed of 300 rpm to 500 rpm for 6 h to 10 h until the mixture is evenly mixed to obtain an electrode slurry with uniform viscosity. The dispersion solvent is N-methyl-2-pyrrolidone (NMP), and the mass ratio of the total solid raw materials of the active material, conductive agent and binder to NMP is 1:(3~5).

[0046] The raw materials are mixed using a solution stirring method. The dispersion effect of NMP solvent ensures uniform mixing of the active materials and conductive agents, guaranteeing electrode uniformity and avoiding localized performance differences. This method achieves uniform mixing of raw materials, is simple to operate, suitable for large-scale electrode coating, and is a mature and universal process in the field.

[0047] S3. The electrode paste is coated onto a conductive current collector resistant to electrolyte corrosion and then dried to obtain the electrode sheet; Specifically, the electrode slurry is uniformly coated onto a conductive current collector resistant to electrolyte corrosion. During the coating process, an external magnetic field perpendicular to the plane of the current collector is applied below the current collector. The magnetic field strength is 0.5T~2T, which induces the sheet-like magnetic conductive material in the slurry to be oriented perpendicularly along the magnetic field direction, thereby constructing a three-dimensional conductive network and ion transport channel perpendicular to the current collector. Finally, the material is vacuum dried in a vacuum drying oven at a temperature of 80℃~120℃ for 12h~24h to completely remove the dispersing solvent. The coating thickness is 100μm~200μm to ensure appropriate electrode loading.

[0048] The conductive current collector resistant to electrolyte corrosion can be any of titanium foil, stainless steel foil, or carbon cloth, without affecting the electrode's performance.

[0049] A vertical external magnetic field induces the orientation of sheet-like magnetic conductive agent, optimizing the high-torque diffusion path of traditional thick electrodes into a low-torque vertical direct channel, significantly shortening the zinc ion diffusion distance. At the same time, a continuous three-dimensional electron transport network is constructed, solving the problems of poor dynamics and severe polarization under high current in traditional thick electrodes, achieving a balance between high load and high rate.

[0050] S4. Press and cut the electrode sheet to obtain the positive electrode; Specifically, after the electrode is dried, it is taken out and pressed with a tablet press at a pressure of 10MPa~20MPa for 1min~3min to improve the density of the electrode; then the electrode is punched into a circular electrode sheet with a diameter of 10mm~12mm by a punching machine to obtain a three-dimensional thick-coated positive electrode.

[0051] Electrodes are fabricated using a coating-pressing process, which allows the active material to adhere tightly to the current collector, improving electrode density, reducing internal resistance, and enhancing electron and ion transport efficiency. This method is mature, easily scaled up for industrial application, and can be directly reused by those skilled in the art in existing production lines.

[0052] The present invention also provides an aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is the three-dimensional thick-coated positive electrode described above, the negative electrode is a zinc sheet, the separator is glass fiber, and the electrolyte is a mixed aqueous solution of zinc salt and manganese salt.

[0053] The specific assembly steps are as follows: In a glove box under an argon atmosphere, assemble the positive electrode, negative electrode, separator, and electrolyte into a button cell. Then, let the cell stand for 6 to 12 hours to allow the electrolyte to fully wet the positive electrode, negative electrode, and separator before conducting a charge-discharge test to achieve zinc ion storage.

[0054] The core invention lies in proposing a three-level synergistic modification strategy of bulk pre-embedding modification, interface coating optimization, and electrode structure reconstruction, which for the first time simultaneously achieves lattice structure optimization, electronic structure regulation, interface stability improvement, and breakthrough in thick electrode dynamics of δ-MnO2 cathode. 1. Bulk phase level: Metal ion pre-intercalation is achieved through a one-step hydrothermal method, and the interlayer spacing expansion and electronic structure regulation are completed simultaneously. This not only stabilizes the layered framework but also enhances the hydrogen ion intercalation activity, breaking through the performance bottleneck of single lattice regulation. 2. Interface level: Atomic-level uniform titanium oxide coating is achieved by using atomic layer deposition technology, which suppresses interfacial side reactions while ensuring rapid ion transport, thus solving the contradiction of "stability and kinetics being mutually exclusive" in traditional coatings. 3. Electrode level: By inducing the vertical orientation of sheet-like conductive agents through magnetic field, a three-dimensional conductive network with low tortuosity is constructed. While increasing the electrode loading and energy density, the reaction kinetics of thick electrodes are greatly improved, solving the problem of "high loading and high rate" that cannot be achieved simultaneously in traditional thick electrodes. 4. The three technologies work together in multiple dimensions to fundamentally and simultaneously solve the three core problems of short cycle life, poor rate performance and low energy density of δ-MnO2 cathode.

[0055] This invention, through a three-level synergistic approach of metal ion pre-intercalation phase modification, ALD coating, and magnetic field-oriented three-dimensional thick electrode, achieves for the first time simultaneous optimization of the lattice structure, regulation of the electronic structure, improvement of interface stability, and breakthrough in thick electrode dynamics of the δ-MnO2 cathode. This differs from existing technologies that rely solely on a single modification strategy to regulate the interlayer spacing. Lattice manipulation: Pre-intercalation of ions expands the interlayer spacing of δ-MnO2 from 0.72 nm in the pure material to 0.75 nm, Zn 2+ The diffusion coefficient was increased by 2 times, solving the problem of Zn. 2+ The problem of high diffusion resistance and slow kinetics was solved, but the layered structure was stabilized and the dissolution of manganese was inhibited. Electronic structure manipulation: By adjusting the p-band center of the O atom, the voltage was optimized from -5.8 eV in pure MnO2 to -5.2 eV in the Cu pre-intercalated material, allowing H... + The adsorption and desorption reach optimal equilibrium, H + The intercalation capacity contribution increased from 65% to 74% for pure materials, solving the problem of existing H-technologies. + The problem of insufficient intercalation activity; Interface regulation: Atomically uniform TiO2 coating suppresses irreversible side reactions at the interface, further reducing the capacity decay rate during cycling; Electrode structure regulation: The three-dimensional vertical conductive network reduces the ion diffusion tortuosity of thick electrodes from above 3.0 to below 1.5, increases the active material loading by 2 to 3 times, and significantly improves the energy density; The synergistic effect of the four regulation methods enables the material to simultaneously achieve high capacity, long cycle life, and excellent rate performance, solving the core defects that existing technologies cannot address at the same time.

[0056] The composite modified δ-MnO2 cathode material of this invention was tested, and the results are as follows: 1. Cyclic performance comparison: Pure δ-MnO2 exhibits significant capacity decay and poor capacity retention after long cycling; the existing Zn pre-intercalated modified manganese dioxide has improved cycling stability, but there is still room for improvement; the three-stage synergistic modified electrode of the present invention exhibits superior cycling stability and still has good capacity retention after long cycling, among which the Cu pre-intercalated material performs the best, significantly better than various existing modification schemes. 2. Rate performance comparison: Pure δ-MnO2 exhibits significant capacity decay under high current conditions and poor rate performance; the composite modified thick-coated electrode of this invention can still maintain a high discharge capacity under high current conditions, and its rate performance is significantly improved compared with the pure material, showing excellent high current charge and discharge characteristics, and is suitable for fast charging application scenarios. 3. Kinetic performance comparison: Pure δ-MnO2 has a relatively high charge transfer impedance and its electrochemical reaction kinetics are relatively slow; the charge transfer impedance of the composite modified thick-coated electrode of this invention is significantly reduced, indicating that this modification scheme can effectively reduce the internal resistance of the electrode and significantly improve the reaction kinetic performance. 4.H + Intercalation capacity comparison: The hydrogen ion intercalation capacity contribution of pure δ-MnO2 is relatively low, and the capacity mainly depends on zinc ion intercalation, resulting in slow reaction kinetics; The hydrogen ion intercalation capacity contribution of the composite modified material of the present invention is significantly improved, indicating that the electronic structure regulation of the present invention effectively enhances the hydrogen ion intercalation activity, which is the core reason for the improvement of material capacity and reaction kinetics. 5. Energy density comparison: Traditional thin electrodes have limited active material loading, resulting in low overall battery energy density; the three-dimensional thick-coated electrode of this invention can significantly increase the active material loading, and the battery energy density is significantly higher than that of traditional thin electrodes.

[0057] Example 1 In this embodiment, the composite modified δ-MnO2 cathode material has K pre-intercalated metal ions. + Specifically, prepare it according to the following steps: Step 1: Weigh out 5 mmol of KMnO4, 5 mmol of MnSO4 and 0.5 mmol of K2SO4 respectively; Step 2: Add the weighed raw materials to 70mL of deionized water and stir at 300rpm for 20min until fully dissolved; Step 3: Transfer to a conventional hydrothermal reactor, seal it, and keep it at 160°C for 10 hours. After the reaction is complete, allow it to cool naturally to room temperature. Step 4: After centrifugation at 8000 rpm for 5 min, wash twice alternately with deionized water and anhydrous ethanol to obtain the precipitate; Step 5: Dry the precipitate under vacuum at 50°C for 10 hours to obtain K. + Pre-embedded δ-MnO2 powder; Step 6: Place the above powder in the ALD reaction chamber, and perform 60 cycles of deposition at 100°C using TiCl4 as the titanium source and H2O as the oxygen source to obtain TiO2-coated K pre-embedded δ-MnO2 powder with a coating thickness of about 3 nm.

[0058] The composite modified δ-MnO2 cathode material obtained above is used to fabricate a three-dimensional thick-coated cathode electrode, specifically by following these steps: S1. Weigh out the composite modified δ-MnO2 cathode material, conductive agent and binder according to the proportion; The mass ratio of K pre-embedded δ-MnO2 to the composite conductive agent is 19:1. The composite conductive agent contains 50% magnetic expanded graphite and 50% conductive carbon black, with a total content of 100%. PVDF binder is added, and the amount of binder is 10% of the total mass of the active and conductive agents. S2. Add 3 mL / g of NMP solvent and stir at 300 rpm for 6 h to obtain a uniform electrode slurry. S3. The electrode paste is coated onto the titanium foil current collector. A vertical magnetic field of 0.8T is applied during the coating process. The coating thickness is 100μm. The electrode is then vacuum dried at 80℃ for 12h and dried to obtain the electrode sheet. S4. Press the coated electrode sheet under a pressure of 10MPa for 1 minute and punch it into a positive electrode with a diameter of 10mm.

[0059] Performance test results: The material maintains a high discharge capacity after long-term cycling at a high current density, and the capacity retention effect is good; it also has excellent rate discharge performance under high current density conditions.

[0060] Example 2 In this embodiment, the composite modified δ-MnO2 cathode material has Cu as the pre-intercalated metal ion. 2+ Specifically, prepare it according to the following steps: Step 1: Weigh out 5 mmol of KMnO4, 5 mmol of MnSO4 and 0.5 mmol of CuSO4 respectively; Step 2: Add the weighed raw materials to 80mL of deionized water and stir at 400rpm for 30min until fully dissolved; Step 3: Transfer to a conventional hydrothermal reactor, seal it, and keep it at 180°C for 12 hours. After the reaction is complete, allow it to cool naturally to room temperature. Step 4: After centrifugation at 10,000 rpm for 8 minutes, wash the precipitate three times alternately with deionized water and anhydrous ethanol to obtain the precipitate. Step 5: Dry the precipitate under vacuum at 60℃ for 12 hours to obtain Cu. 2+ Pre-embedded δ-MnO2 powder; Step 6: Place the above powder in the ALD reaction chamber, and perform 100 cycles of deposition at 120°C using TiCl4 as the titanium source and H2O as the oxygen source to obtain TiO2-coated Cu pre-embedded δ-MnO2 powder with a coating thickness of about 5 nm.

[0061] The above-obtained composite modified δ-MnO2 cathode material is used to fabricate a cathode electrode, specifically by following these steps: S1. Weigh out the composite modified δ-MnO2 cathode material, conductive agent and binder according to the proportion; The mass ratio of Cu pre-embedded δ-MnO2 to the composite conductive agent is 97:3. The composite conductive agent contains 60% magnetic graphene and 40% Super P, with a total content of 100%. PVDF binder is added, with the binder amount being 10% of the total mass of the active and conductive agents. S2. Add 4 mL / g of NMP solvent and stir at 400 rpm for 8 hours to obtain a uniform electrode slurry. S3. The electrode paste is coated onto the titanium foil current collector. A 1T vertical magnetic field is applied during the coating process. The coating thickness is 150μm. The electrode is then vacuum dried at 100℃ for 18h and dried to obtain the electrode sheet. S4. Press the coated electrode sheet under a pressure of 15MPa for 2 minutes and punch it into a positive electrode with a diameter of 11mm.

[0062] Performance test results: The material can maintain a high discharge capacity after long-term cycling at high current density, and the capacity retention effect is excellent; it also has excellent rate discharge performance under high current charge and discharge conditions.

[0063] Example 3 In this embodiment, the composite modified δ-MnO2 cathode material has Na as the pre-intercalated metal ion. + Specifically, prepare it according to the following steps: Step 1: Weigh out 5 mmol of KMnO4, 5 mmol of MnSO4 and 0.5 mmol of Na2SO4 respectively; Step 2: Add the weighed raw materials to 90mL of deionized water and stir at 500rpm for 40min until fully dissolved; Step 3: Transfer to a conventional hydrothermal reactor, seal it, and keep it at 200°C for 14 hours. After the reaction is complete, allow it to cool naturally to room temperature. Step 4: After centrifugation at 12000 rpm for 10 min, wash the precipitate four times alternately with deionized water and anhydrous ethanol to obtain the precipitate; Step 5: Dry the precipitate under vacuum at 70℃ for 14 hours to obtain Na. + Pre-embedded δ-MnO2 powder; Step 6: Place the above powder in the ALD reaction chamber, and perform 150 cycles of deposition at 150°C using TiCl4 as the titanium source and H2O as the oxygen source to obtain TiO2-coated Na pre-intercalated δ-MnO2 powder with a coating thickness of about 8 nm.

[0064] The above-obtained composite modified δ-MnO2 cathode material is used to fabricate a cathode electrode, specifically by following these steps: S1. Weigh out the composite modified δ-MnO2 cathode material, conductive agent and binder according to the proportion; The mass ratio of Na pre-intercalated δ-MnO2 to the composite conductive agent is 99:1. The composite conductive agent consists of 70% magnetic graphene and 30% acetylene black, with a total content of 100%. PVDF binder is added, with the binder amount being 10% of the total mass of the active and conductive agents. S2. Add 5 mL / g of NMP solvent and stir at 500 rpm for 10 h to obtain a uniform electrode slurry. S3. The electrode paste is coated onto the titanium foil current collector. A vertical magnetic field of 1.5T is applied during the coating process. The coating thickness is 200μm. The electrode is then vacuum dried at 120℃ for 24h and then dried to obtain the electrode sheet. S4. Press the coated electrode sheet under a pressure of 20MPa for 3 minutes and punch it into a positive electrode with a diameter of 12mm.

[0065] Performance test results: The material can maintain a high discharge capacity after long-term cycling at a high current density, and the capacity retention effect is good; it also has stable rate discharge performance under high current charge and discharge conditions.

[0066] Example 4 In this embodiment, the composite modified δ-MnO2 cathode material has K pre-embedded between the δ-MnO2 layers. + Furthermore, the surface is coated with amorphous TiO2, with a coating thickness of 2nm.

[0067] The above-mentioned composite modified δ-MnO2 cathode material is prepared according to the following steps: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; In step 1, the molar ratio of manganese source to pre-intercalated metal salt is 1:0.05; the manganese source is manganese chloride, and the pre-intercalated metal salt is potassium chloride. Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Specifically, the manganese source and the pre-intercalated metal salt were added separately to deionized water and stirred at 300 rpm for 20 minutes until the manganese source and the pre-intercalated metal salt were completely dissolved, resulting in a homogeneous and transparent mixed solution; the volume ratio of the manganese source to the deionized water was 1 mmol: 7 mL. Step 3: Perform the hydrothermal reaction; Specifically, the manganese source and the pre-intercalated metal salt solution are sealed in a hydrothermal reactor, and then the reactor is placed in a forced-air drying oven. The reaction is carried out at 160°C for 10 hours. After the reaction is completed, the oven is closed and the product is allowed to cool naturally to room temperature. Step 4: Obtain the precipitate by centrifugation and washing; Specifically, the mixture obtained after the hydrothermal reaction is transferred to a centrifuge tube, placed in a high-speed centrifuge, and centrifuged at 8000 rpm for 5 minutes to separate the precipitate and supernatant. The precipitate is then washed twice alternately with deionized water and anhydrous ethanol to remove any remaining unreacted impurity ions. Step 5: Vacuum dry the precipitate to obtain δ-MnO2 powder pre-embedded with metal ions; Specifically, the washed precipitate was transferred to a vacuum drying oven and dried under vacuum at 50°C for 10 hours to remove residual solvent, thereby obtaining metal ion pre-intercalated δ-MnO2 powder. Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material; The amorphous metal oxide layer is amorphous TiO2, the titanium source is titanium tetrachloride TiCl4, the oxygen source is deionized water, and the carrier gas and purge gas are high-purity argon. Each deposition cycle consists of titanium source pulse, argon purge, oxygen source pulse, and argon purge. Specifically, the metal ion pre-embedded δ-MnO2 powder obtained in step 5 is spread evenly in the closed vacuum process chamber of the atomic layer deposition equipment. At a deposition temperature of 80°C, metal source pulse and oxygen source pulse reactions are alternately performed. The coating layer thickness is adjusted by controlling the number of deposition cycles to obtain a metal ion pre-embedded δ-MnO2 cathode material coated with an amorphous metal oxide layer, i.e., composite modified δ-MnO2 cathode material.

[0068] Example 5 In this embodiment, the composite modified δ-MnO2 cathode material has Cu pre-embedded between the δ-MnO2 layers. 2+ Furthermore, the surface is coated with amorphous TiO2, with a coating thickness of 8 nm.

[0069] The above-mentioned composite modified δ-MnO2 cathode material is prepared according to the following steps: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; In step 1, the molar ratio of manganese source to pre-intercalated metal salt is 1:0.1; the manganese source is manganese nitrate, and the pre-intercalated metal salt is copper nitrate. Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Specifically, the manganese source and the pre-intercalated metal salt were added separately to deionized water and stirred at 400 rpm for 30 minutes until the manganese source and the pre-intercalated metal salt were completely dissolved, resulting in a homogeneous and transparent mixed solution; the volume ratio of the manganese source to the deionized water was 1 mmol: 8 mL. Step 3: Perform the hydrothermal reaction; Specifically, the manganese source and the pre-intercalated metal salt solution are sealed in a hydrothermal reactor, and then the reactor is placed in a forced-air drying oven. The reaction is carried out at 180°C for 12 hours. After the reaction is completed, the oven is closed and the product is allowed to cool naturally to room temperature. Step 4: Obtain the precipitate by centrifugation and washing; Specifically, the mixture obtained after the hydrothermal reaction is transferred to a centrifuge tube, placed in a high-speed centrifuge, and centrifuged at 10,000 rpm for 8 minutes to separate the precipitate and supernatant. The precipitate is then washed 5 times alternately with deionized water and anhydrous ethanol to remove residual unreacted impurity ions. Step 5: Vacuum dry the precipitate to obtain δ-MnO2 powder pre-embedded with metal ions; Specifically, the washed precipitate was transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours to remove residual solvent, thereby obtaining metal ion pre-intercalated δ-MnO2 powder. Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material; The amorphous metal oxide layer is amorphous TiO2, the titanium source is titanium tetrachloride TiCl4, the oxygen source is deionized water, and the carrier gas and purge gas are high-purity argon. Each deposition cycle consists of titanium source pulse, argon purge, oxygen source pulse, and argon purge. Specifically, the metal ion pre-embedded δ-MnO2 powder obtained in step 5 is spread evenly in the closed vacuum process chamber of the atomic layer deposition equipment. At a deposition temperature of 130°C, metal source pulse and oxygen source pulse reactions are alternately performed. The coating layer thickness is adjusted by controlling the number of deposition cycles to obtain a metal ion pre-embedded δ-MnO2 cathode material coated with an amorphous metal oxide layer, i.e., a composite modified δ-MnO2 cathode material.

[0070] Example 6 In this embodiment, the composite modified δ-MnO2 cathode material has Na pre-intercalated between the δ-MnO2 layers. + Furthermore, the surface is coated with amorphous TiO2, with a coating thickness of 10 nm.

[0071] The above-mentioned composite modified δ-MnO2 cathode material is prepared according to the following steps: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; In step 1, the molar ratio of manganese source to pre-intercalated metal salt is 1:0.15; the manganese source is manganese acetate, and the pre-intercalated metal salt is sodium chloride. Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Specifically, the manganese source and the pre-intercalated metal salt were added separately to deionized water and stirred at 500 rpm for 40 minutes until the manganese source and the pre-intercalated metal salt were completely dissolved, resulting in a homogeneous and transparent mixed solution; the volume ratio of the manganese source to the deionized water was 1 mmol: 9 mL. Step 3: Perform the hydrothermal reaction; Specifically, the manganese source and the pre-intercalated metal salt solution are sealed in a hydrothermal reactor, and then the reactor is placed in a forced-air drying oven. The reaction is carried out at 200°C for 14 hours. After the reaction is completed, the oven is closed and the product is allowed to cool naturally to room temperature. Step 4: Obtain the precipitate by centrifugation and washing; Specifically, the mixture obtained after the hydrothermal reaction is transferred to a centrifuge tube, placed in a high-speed centrifuge, and centrifuged at 12,000 rpm for 10 minutes to separate the precipitate and supernatant. The precipitate is then washed four times alternately with deionized water and anhydrous ethanol to remove any remaining unreacted impurity ions. Step 5: Vacuum dry the precipitate to obtain δ-MnO2 powder pre-embedded with metal ions; Specifically, the washed precipitate was transferred to a vacuum drying oven and dried under vacuum at 70°C for 14 hours to remove residual solvent, thereby obtaining metal ion pre-intercalated δ-MnO2 powder. Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material; The amorphous metal oxide layer is amorphous TiO2, the titanium source is titanium tetrachloride TiCl4, the oxygen source is deionized water, and the carrier gas and purge gas are high-purity argon. Each deposition cycle consists of titanium source pulse, argon purge, oxygen source pulse, and argon purge. Specifically, the metal ion pre-embedded δ-MnO2 powder obtained in step 5 is spread evenly in the closed vacuum process chamber of the atomic layer deposition equipment. At a deposition temperature of 150°C, metal source pulse and oxygen source pulse reactions are alternately performed. The coating layer thickness is adjusted by controlling the number of deposition cycles to obtain a metal ion pre-embedded δ-MnO2 cathode material coated with an amorphous metal oxide layer, i.e., a composite modified δ-MnO2 cathode material.

Claims

1. A method for preparing composite modified δ-MnO2 cathode material, characterized in that, The specific steps are as follows: Step 1: Weigh out the manganese source and the pre-intercalated metal salt by molar ratio; Step 2: Add the manganese source and the pre-intercalated metal salt to deionized water and stir until fully dissolved; Step 3: Perform the hydrothermal reaction; Step 4: Obtain the precipitate by centrifugation and washing; Step 5: Vacuum dry the precipitate to obtain δ-MnO2 powder pre-embedded with metal ions; Step 6: An amorphous metal oxide layer is coated onto the metal ion pre-embedded δ-MnO2 powder using an atomic layer deposition coating process to obtain a composite modified δ-MnO2 cathode material.

2. The method for preparing the composite modified δ-MnO2 cathode material according to claim 1, characterized in that, In step 1, the molar ratio of manganese source to pre-intercalated metal salt is 1:(0.05~0.15). The principle for selecting the manganese source is that it can synthesize δ-MnO2 by hydrothermal method, and the pre-intercalated ion of the pre-intercalated metal salt is any one of potassium ion, copper ion, and sodium ion.

3. The method for preparing the composite modified δ-MnO2 cathode material according to claim 1, characterized in that, Step 2 specifically involves adding the manganese source and the pre-intercalated metal salt to deionized water and stirring at a stirring speed of 300 rpm to 500 rpm for 20 min to 40 min until the manganese source and the pre-intercalated metal salt are completely dissolved, resulting in a uniform and transparent mixed solution; the volume ratio of the manganese source to the deionized water is 1 mmol: (7 to 9) mL. Step 3 specifically involves: sealing the mixed solution of manganese source and pre-intercalated metal salt in a hydrothermal reactor, then placing the reactor in a forced-air drying oven and maintaining the temperature at 160℃~200℃ for 10h~14h. After the reaction is completed, the oven is closed and the mixture is allowed to cool naturally to room temperature before the reaction product is removed. Step 4 specifically involves: transferring the mixture obtained after the hydrothermal reaction into a centrifuge tube, placing it in a high-speed centrifuge, and centrifuging it at a speed of 8000 rpm to 12000 rpm for 5 min to 10 min to separate the precipitate and the supernatant. The precipitate is then washed 2 to 4 times alternately with deionized water and anhydrous ethanol to remove any residual unreacted impurity ions. Step 5 specifically involves: transferring the washed precipitate to a vacuum drying oven and drying it under vacuum at a temperature of 50℃~70℃ for 10h~14h to remove residual solvent and obtain metal ion pre-intercalated δ-MnO2 powder. Step 6 specifically involves: spreading the metal ion pre-embedded δ-MnO2 powder obtained in step 5 in the sealed vacuum process chamber of the atomic layer deposition equipment, and alternating metal source pulse and oxygen source pulse reactions at a deposition temperature of 80℃~150℃. By controlling the number of deposition cycles, the coating layer thickness is adjusted to 2nm~10nm to obtain an amorphous metal oxide layer coated metal ion pre-embedded δ-MnO2 cathode material, i.e., a composite modified δ-MnO2 cathode material.

4. The method for preparing the composite modified δ-MnO2 cathode material according to claim 1, characterized in that, In step 6, the coating thickness is 2nm to 10nm.

5. A composite modified δ-MnO2 cathode material, characterized in that, The composite modified δ-MnO2 cathode material was prepared according to the preparation method of any one of claims 1 to 4, wherein metal ions are pre-embedded in the interlayer of δ-MnO2 and the surface is coated with an amorphous metal oxide layer, and the metal ions are K. + Cu 2+ Na + Any one of them, the thickness of the metal oxide coating layer is 2nm~10nm.

6. A three-dimensional thick-coated positive electrode, characterized in that, Including the composite modified δ-MnO2 cathode material as described in claim 5.

7. A method for preparing a three-dimensional thick-coated positive electrode, characterized in that, The specific steps are as follows: S1. Weigh out the composite modified δ-MnO2 cathode material, composite conductive agent and binder according to the proportion; S2. The composite modified δ-MnO2 cathode material, composite conductive agent and binder are added to the dispersion solvent and mixed. The mixture is stirred until it is uniform to obtain the electrode slurry. S3. Under the assistance of a magnetic field, the electrode paste is coated onto a conductive current collector that is resistant to electrolyte corrosion and then dried to obtain an electrode sheet. S4. Press and cut the electrode sheet to obtain a three-dimensional thick-coated positive electrode.

8. The method for preparing a three-dimensional thick-coated positive electrode according to claim 7, characterized in that, The mass ratio of the composite modified δ-MnO2 cathode material to the composite conductive agent is 19:1 to 99:1, and the binder accounts for 8% to 12% of the total mass of the composite modified δ-MnO2 cathode material and the composite conductive agent. The composite conductive agent is composed of sheet-like magnetic conductive material and granular conductive carbon. The sheet-like magnetic conductive material accounts for 40% to 70% of the total mass of the composite conductive agent, and the remainder is granular conductive carbon.

9. The method for preparing a three-dimensional thick-coated positive electrode according to claim 8, characterized in that, S3 specifically involves uniformly coating the electrode slurry onto a conductive current collector resistant to electrolyte corrosion. During the coating process, an external magnetic field perpendicular to the plane of the current collector is applied below the current collector, with a magnetic field strength of 0.5T~2T. This induces the sheet-like magnetic conductive material in the slurry to align perpendicularly to the magnetic field direction, constructing a three-dimensional conductive network and ion transport channels perpendicular to the current collector. Finally, the material is vacuum dried in a vacuum drying oven at a temperature of 80℃~120℃ for 12h~24h to completely remove the dispersing solvent. The coating thickness is 100μm~200μm.

10. An aqueous zinc-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is the three-dimensional thick-coated positive electrode as described in claim 6, the negative electrode is a zinc sheet, the separator is glass fiber, and the electrolyte is a mixed aqueous solution of zinc salt and manganese salt.